Pilotprojekt zur Nachwuchsgewinnung – Neues Wahlfach an der Universitätsmedizin Göttingen (Zeitschrift für Orthopädie und Unfallchirurgie, 2013)
The Young Forum of the German Society of Orthopedics and Traumatology is an interest group of young orthopedics and trauma surgeons in Germany. Besides dealing with topics of political interest, the group tries to arouse enthusiasm and interest for musculosceletal surgery by means of new lectures and teaching methods.An example is the newly invented optional subject for students at the Medical School in Göttingen (Germany). The idea for such a new teaching offer was built by the Young Forum itself. The optional subject was on the syllabus for the first time this year and the organization was done by the university Department of Trauma Surgery, Plastic and Reconstructive Surgery. The course is divided in two main parts: a theoretical (16 hours) and a practical (10 hours) one. A good ratio of lectures, skills stations and workshops was on choice. This article explains the course in detail and shows a first evaluation result.
Keywords: pilot scheme; young health professionals; Young Forum; German Society of Orthopedics and Traumatology